Комплексная концепция виртуального ортогнатического планирования у пациентов, впервые проходящих хирургическое вмешательство (Open Herald: Periodical of Methodical Research, 2024)
To date, the problem of traumatic injuries of the middle The "surgery first" concept is becoming increasingly popular in orthognathic surgery as it offers major benefits such as reduced treatment duration and increased patient satisfaction by eliminating preoperative orthodontic decompensation phases. Here, we present a new interdisciplinary pathway for fully virtual orthodontic surgical planning in the surgical setting using a 3D-printed cutting template and a customized maxillary implant for Le Fort I osteotomy, as well as a CAD/CAM-based definitive stereolithography splint. Patient data obtained from cranial cone beam computed tomography and full dental scans were processed using OnyxCeph3TM software (Image Instruments). The orthodontist and oral surgeon performed a joint computerized surgical simulation to determine three-dimensional movements of the maxilla and mandible. In a separate virtual planning session, the surgeon developed a customized maxillary template and implant for precise intraoperative transfer (Geomagic Freeform Plus software, 3DSystems). The final 3D printed CAD/CAM splint was fabricated by the orthodontist and used to accurately reduce the mandible